2002
DOI: 10.1152/ajpheart.00780.2001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of alcohol dehydrogenase exacerbates ethanol-induced contractile defect in cardiac myocytes

Abstract: . Overexpression of alcohol dehydrogenase exacerbates ethanol-induced contractile defect in cardiac myocytes. Am J Physiol Heart Circ Physiol 282: H1216-H1222, 2002. First published December 13, 2001; 10.1152/ajpheart.00780.2001.-Alcoholic cardiomyopathy is characterized by impaired ventricular function although its toxic mechanism is unclear. This study examined the impact of cardiac overexpression of alcohol dehydrogenase (ADH), which oxidizes ethanol into acetaldehyde (ACA), on ethanol-induced cardiac cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
75
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 28 publications
14
75
1
Order By: Relevance
“…2,3,25 Our earlier findings revealed that overexpression of ADH in the heart led to enhanced cardiac acetaldehyde exposure and augmented alcohol intake-induced cardiomyopathy manifested as cardiac hypertrophy, protein damage, ER stress, oxidative stress and mitochondrial damage. 9,22,26,27 Results from our current study confirmed cardiac acetaldehyde accumulation had a more pronounced effect in ADH mice (despite comparable levels of blood alcohol and acetaldehyde between FVB and ADH mice) following chronic alcohol intake. More importantly, data from our present study provided evidence for the first time that acetaldehyde through revealed that ethanol/acetaldehyde-induced autophagosome accumulation may be more likely due to an inhibition of the late-stage autophagic flux as opposed to induction of the early-stage autophagosome formation.…”
Section: Discussionsupporting
confidence: 76%
“…2,3,25 Our earlier findings revealed that overexpression of ADH in the heart led to enhanced cardiac acetaldehyde exposure and augmented alcohol intake-induced cardiomyopathy manifested as cardiac hypertrophy, protein damage, ER stress, oxidative stress and mitochondrial damage. 9,22,26,27 Results from our current study confirmed cardiac acetaldehyde accumulation had a more pronounced effect in ADH mice (despite comparable levels of blood alcohol and acetaldehyde between FVB and ADH mice) following chronic alcohol intake. More importantly, data from our present study provided evidence for the first time that acetaldehyde through revealed that ethanol/acetaldehyde-induced autophagosome accumulation may be more likely due to an inhibition of the late-stage autophagic flux as opposed to induction of the early-stage autophagosome formation.…”
Section: Discussionsupporting
confidence: 76%
“…Ventricular myocytes were isolated from FVB or OVE26 mouse hearts according to a previously described method (17). In brief, after ketamine-xylazine sedation, mouse hearts were rapidly removed and perfused with Krebs-Henseleit bicarbonate buffer containing (in mM): 118 NaCl, 4.…”
Section: Cell Isolation Proceduresmentioning
confidence: 99%
“…The mechanical properties of ventricular myocytes were assessed using a MyoCam 1 video detection system (IonOptix Corporation, Milton, MA) as described previously (17). In brief, cells were placed in a chamber mounted on the stage of an inverted microscope (Olympus IX-70) and superfused with a buffer containing (in mM): 131 NaCl, 4 KCl, 1 CaCl 2 , 1 MgCl 2 , 10 glucose, 10 HEPES, at pH 7.4.…”
Section: Cells Shortening=relengtheningmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed increased sensitivity to low calcium in perfused hearts from the transgenic mice (13). Avertin is an alcohol-based anesthetic, and alcohol reduces intracellular calcium in mouse myocytes (4). This may explain in part the increased sensitivity to avertin in the transgenic mice, although because dobutamine (which increases intracellular calcium) only partially restores contractility, other effects of avertin are also likely present.…”
Section: Discussionmentioning
confidence: 99%